2019
DOI: 10.17520/biods.2019166
|View full text |Cite
|
Sign up to set email alerts
|

Advances in LiDAR technology in the field of animal ecology

Abstract: LiDAR (light detection and ranging), a fairly new active remote sensing technology, is being widely used in the field of animal ecology by more and more scholars due to the recent development where forest parameters can be extracted and inverted from LiDAR. In this paper, we review the advances in forest parameter extraction from LiDAR and its many applications in studying wildlife habitat. We also analyze current research on forest parameter inversion algorithms based on LiDAR, mainly in forestry research, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the vicinity of the camera point, a 20 m × 20 m area was selected and scanned using lidar equipment (PARACOSM PX-80 HANDHELD MOBILE LiDAR, PX-80, Topsfield, MA, USA). Using the LIDAR360 software, we classified and extracted information on tree species, shrub coverage, tree height, and leaf area index [ 26 ]. Similarly, a manual vegetation survey was conducted within a 20 m × 20 m area near the camera point to record transparency, concealment, and the diversity and quantity of herbs, shrubs, and trees.…”
Section: Methodsmentioning
confidence: 99%
“…In the vicinity of the camera point, a 20 m × 20 m area was selected and scanned using lidar equipment (PARACOSM PX-80 HANDHELD MOBILE LiDAR, PX-80, Topsfield, MA, USA). Using the LIDAR360 software, we classified and extracted information on tree species, shrub coverage, tree height, and leaf area index [ 26 ]. Similarly, a manual vegetation survey was conducted within a 20 m × 20 m area near the camera point to record transparency, concealment, and the diversity and quantity of herbs, shrubs, and trees.…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, three‐dimensional forest structure could directly and indirectly indicate the food resources and the foodscapes of large herbivores (Li et al. 2019). Although the resolution of the LiDAR scan at this stage is still not enough to precisely quantify shrubs and herbs, with the continuous updating of technology and the deepening of research, it will be possible to quantify the foodscape through LiDAR.…”
Section: Figurementioning
confidence: 99%
“…With the rapid development of UAV and ground-based LiDAR monitoring technology, new opportunities have been provided for the study of the scale-dependent relationship between wildlife and habitat (Bergen et al 2009;Davies & Asner 2014;Simonson et al 2014). Li-DAR monitoring could quickly and accurately provide the three-dimensional forest structure of the habitat where wildlife lives and in-depth studies on habitat selection and utilization in wildlife ecology have been promoted (Li et al 2019). The latest research, through the comprehensive applications of LiDAR to detect three-dimensional forest structure and automatic camera monitoring data, has shown that mammals are most sensitive to the covariates of forest vertical and horizontal characteristics and prefer to choose environments with complex structures, emphasizing that the identification of mammalian priority restoration areas through three-dimensional forest structure is superior to simple forest classification (Deere et al 2020).…”
mentioning
confidence: 99%